ADDENDUM TO MARSH (2014): Pithecia hirsuta Spix, 1823 AND Pithecia inusta Spix, 1823 ARE SYNONYMS - SERRANO-VILLAVICENCIO, José Eduardo (2024)
The Saki monkeys, genus Pithecia Desmarest, 1804, have undergone drastic taxonomic changes in a 2014 revision of the genus. In this revision, Pithecia hirsuta Spix, 1823 and P. inusta Spix, 1823 were considered as valid, although both species have been widely considered synonymous with P. monachus. Nonetheless, here we demonstrate, by reviewing the original descriptions of both species, that P. inusta cannot be applied to the Peruvian populations of Pithecia inhabiting primarily the Ucayali River watershed since the original concept of this species, as well as its type locality did not include its putative geographic range. In fact, the area falls completely outside the expedition's itinerary that collected the holotype. Thus, to preserve stability until further evidence is furnished, the above-mentioned Pithecia populations should be regarded as P. monachus.